Multifaceted Study on a Cytochalasin Scaffold: Lessons on Reactivity, Multidentate Catalysis, and Anticancer Properties. Issue 62 (21st October 2018) - Zaghouani, Mehdi; Gayraud, Oscar; Jactel, Vincent; Prévost, Sébastien; Dezaire, Ambre; Sabbah, Michèle; Escargueil, Alexandre; Lai, Thanh‐Lan; Le Clainche, Christophe; Rocques, Nathalie; Romero, Stéphane; Gautreau, Alexis; et al.
Abstract: An intramolecular Diels–Alder (IMDA) reaction efficiently accelerated by Schreiner's thiourea is reported, to build a functionalized cytochalasin scaffold (periconiasin series) for biological purposes. DFT calculation highlighted a unique multidentate cooperative hydrogen bonding in this catalysis. The deprotection end game afforded a collection of diverse structures and showed the peculiar reactivity of the Diels–Alder cycloadducts upon functionalization. Biological studies revealed strong cytotoxicity of a few compounds on breast cancer cell lines while actin polymerization is preserved. Abstract : A functionalized cytocalasin scaffold has been prepared by an intramolecular Diels–Alder reaction accelerated by Schreiner's thiourea. The catalytic effect, a multidentate cooperative hydrogen bonding, has been revealed by DFT calculations. Some of the obtained periconiasin‐inspired compounds show strong cytotoxicity against breast cancer cells (see graphic).